PENERAPAN OPEN SHORTEST PATH FIRST (OSPF) UNTUK MENENTUKAN JALUR TERBAIK DALAM JARINGAN - Hari Antoni Musril (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2017)
Large-scale computer networks often face problems in data communications. Data transmission takes a long time due to the inappropriate selection of routing protocols. The selected routing protocol can not provide the best alternative path for get through the data packets. This research tested the ability of Open Shortest Path First (OSPF) routing protocol in the selection of the best path. As a comparison the chosen routing protocol is Routing Information Protocol version 2 (RIPv2). This research compares the best path generated by OSPF and RIPv2. OSPF is a routing protocol that often used in medium and large scale networks. OSPF distributes routing information between system autonomous routers (AS). OSPF is routing protocol that use link-state algorithm to build and calculate the shortest path to all known destination. Link-state algorithms are also known as dijkstra algorithm or shortest path first (SPF) algorithms. Dijkstra's algorithm is applied in the OSPF protocol to choose the best route to be taken by a data packet from a source address in order to arrive at the destination address with the value of the unit load (cost metric) the smallest. In graph theory, Dijkstra's algorithm is used to choose the shortest path between two vertices of a graph that is a representation of the network topology. Whereas RIPv2 is a distance vector protocol that uses a hop count in it's measurement. Path that have a lower hop count will be selected for get through the data packets. Based on experiments that have been carried out, the OSPF routing protocol can provide a selection of the best route (best path) to deliver data packets. While RIPv2 can not specifically generate the best path.